Factors that affect the food production in Malaysia - Lim, Yann Torng (2022)
This paper is investigating the relationship between employment in agriculture, agricultural land, population growth, consumer price index, fertilizer consumption, and food production index. Food and Agriculture Organization (FAO) has estimated the amount of food will need to raise at least 60 percent more in order to feed the future growing population. In the recent world, many factors will affect the food production of a country. Countries that have an issue with the food production system will lead to different issues and problems in society, economy, and politics. Relying on food imports will reduce the ability of self-sufficiency of a country. Besides, the price of food imports might have fluctuated due to the appreciation and depreciation of the currency. In 2019, food imports for Malaysia are about 60% of its food needs, which shows food security is a major issue in Malaysia. In this paper food production index act as the representative of food security, and the VECM model is used to determine the relationship between the variables. The findings of this study show that there are only 2 variables that have a significant relationship with the food production which are employment in agriculture (EA) and consumer price index (CPI), other variables like agricultural land (AL), population growth (PG), and fertilizer consumption (FC) do not have a significant relationship with food production index (FPI).